PENGARUH KECERDASAN EMOSIONAL DAN ETOS KERJA TERHADAP KINERJA KARYAWAN PT. MAJU EXSPRES PALEMBANG - Herman Efrizal; Suharti . (JURNAL KOMPETITIF, 2019)
ABSTRACT                This study basically discusses the influence of emotional intelligence and work ethic on employee performance at PT. Forward Palembang Exspres. The population and sample studied were 52 people. From the results of the study of emotional intelligence and work ethic simultaneously have a significant influence on the performance of employees where the equation obtained from the results of multiple linear regression is Y = 21,132 + 0.098 X1 + 0.583 X2 + e. The coefficient of determination (R2) is 0.564 or 56.4% which means that 56.4% of performance is influenced by emotional intelligence and work ethic. While the remaining 43.6% is influenced by other factors not examined in this study. Such as the work environment, work discipline, education, income, social security, employment opportunities, capacity building and production facilities. F test results indicate the influence of emotional intelligence and work ethic on the performance of employees of PT. Forward Palembang Exspres. T-test results of emotional intelligence affect employee performance and work ethic affect employee performance at PT.Maju Exspres Palembang. Keywords: Emotional Intelligence, Work Ethic, Performance